Removal of crystal violet from aqueous solution using surfactant modified glass waste: kinetic, isotherm, and thermodynamic studies. Issue 38 (14th August 2016) - Sooki, Shayan; Norouzbeigi, Reza; Rahbar-Kelishami, Ahmad
Abstract: In this study, powdered glass waste was modified by sodium dodecyl sulfate and used as an adsorbent for the removal of crystal violet from aqueous solution for the first time. The effect of the main adsorption parameters, kinetics, and adsorption isotherms was evaluated. Optimal conditions have been determined using Taguchi experimental design. The best conditions were found at 0.05 mg of adsorbent, 50 mg/L dye concentration, and pH value of 9. The maximum sorption uptake was 28.3 mg/g at 321 K. Adsorption data were well described by the Freundlich model. Calculated thermodynamic parameters showed the endothermic and spontaneous nature of the adsorption process. A mass transfer model (intraparticle diffusion) was applied to the experimental data to examine the mechanism of the rate-controlling step.